Pharmacological and mechanical management of calcium channel blocker toxicity. (27th August 2018) - Fadhlillah, Fiqry; Patil, Shashank
Abstract : Cardiovascular instability associated with calcium channel blocker toxicity comprises a small percentage of overdose presentations, yet they are associated with a high mortality rate. We detail the management of a 64-year-old man who took an intentional overdose of 840 mg nimodipine. We include the treatment he received and highlight the scarcity of evidence behind the use of gastric decontamination, calcium, glucagon, intravenous lipid emulsion, high-dose insulin therapy, sodium bicarbonate, vasopressors and methylene blue in calcium channel blocker toxicity. Additionally, the article explores the use of electrical pacing and venoarterial extracorporeal membrane oxygenation (VA-ECMO). Following successful weaning of VA-ECMO, the patient was successfully extubated but remained neurologically impaired due to hypoxic-ischaemic brain injury, critical care polyneuropathy and renal failure requiring dialysis. He has cerebral performance category 3; he has mild cognitive impairment but able to perform some activities of daily living independently and communicate his thoughts and needs. He requires no respiratory or cardiovascular support.